Trend analysis of crimes committed against persons in Ughelli Metropolis, Delta State, Nigeria - OKPUVWIE, Ejuvweyere Jonathan; TOHOZIN, Coovi Aime Bernadin; AKINYEDE, Joseph Olusola (Socialscientia: Journal of Social Sciences and Humanities, 2023)
Crime is an unacceptable practice that destabilizes any society. The activities of criminals have resulted in many people being killed and injured over time across the world including Nigeria. In Ughelli, Delta State, Nigeria, the incidences of crime have reached an alarming and a dangerous stage and this has become timely to find an appropriate solution to the problem. The objective of this study is to examine the trends of crimes committed against people in the metropolis of Ughelli from 2016 to 2020 with a view to determining the crime trend from the same period for enhanced security. Primary and secondary data were collected for the study and were analyzed with the aid of SPSS. The obtained shapefiles were used in ArcGIS version 10.8 for the attainment of the set objective for the study. A total of 20 different crime types were identified from the study, while 192 crime cases were recorded in the study area between 2016 and 2020.The results obtained from the study were presented in tabular and graphical form. The study shows that there is a substantial correlation between crime occurrence and days of the weeks, times and even seasons across space. The study further revealed crimes like rape, assault, murder, impersonation and kidnapping among others as some of the common crimes committed against persons in the study area. Above all, the study recommends among others that the federal government of Nigeria should locate more police stations in metropolitan areas across the country in general and in Ughelli in particular for enhanced security.